2014
DOI: 10.3389/fphar.2014.00160
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of G-quadruplex structures to pharmacogenetics

Abstract: G-quadruplexes are non-canonical secondary structures formed within nucleic acids that are involved in modulating cellular processes such as replication, gene regulation, recombination and epigenetics. Within genes, there is mounting evidence of G-quadruplex involvement in transcriptional and post transcriptional regulation. We report the presence of potential G-quadruplex motifs within relevant sites of some important pharmacogenes and discuss the possible implications of this on the function and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…This gene serves as an on and off switch that regulates cell differentiation and apoptosis. In another study, G4 ligands have been shown to forestall the incorporation of the HIV genome into the host genome by binding to and stabilizing G4s in the multi-domain HIV integrase enzyme ( Cree and Kennedy, 2014 ; Bala et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene serves as an on and off switch that regulates cell differentiation and apoptosis. In another study, G4 ligands have been shown to forestall the incorporation of the HIV genome into the host genome by binding to and stabilizing G4s in the multi-domain HIV integrase enzyme ( Cree and Kennedy, 2014 ; Bala et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are over 200 crystal and NMRderived structures of quadruplexes present in the protein data bank. These G-quadruplex structures and their ligand complexes have been reviewed elsewhere in detail [8][9][10][11][12][13][14][15][16][17][18] . Positively charged alkali metal ions are essentially required for the stabilisation of the quadruplexes 19 .…”
Section: Review Articlementioning
confidence: 99%
“…It is well known that G-quartet structures play crucial roles in various cellular processes like in maintaining chromosomal ends, transcription, translation etc. [72] , along with their wide application in nanotechnology because of their self-assembly formation and stability [85] , [86] , [87] . The role of G-quadruplex structure in neurodegenerative diseases and non-coding transcriptome has also recently been reported [88] .…”
Section: Biological Applications Of Alternative Dna Structuresmentioning
confidence: 99%